İstanbul’da bir birinci basamak sağlık kuruluşunda kronik hastalıklardan korunmada kaçırılmış fırsatlar - (:unkn) unknown (My University, 2011)
AMAÇ: Araştırmanın amacı İstanbul‟da bir sağlık ocağında kronik hastalıklar ve risk faktörleri ile ilgili kaçırılmış fırsatların araştırılmasıdır. YÖNTEM: Tanımlayıcı tipteki bu araştırma İstanbul‟da bir birinci basamak sağlık kuruluşuna bir aylık süre içerisinde başvuran 500 kişi ile yürütüldü. Katımcılar 2006 Birinci Basamak Rehberine göre, ana risk faktörleri (sigara içme, obezite, diyabetes mellitus, hipertansiyon, ailede koroner kalp hastalığı, glisemik düzey ve kolesterol düzeyi) ve düzenli egzersiz yapma açısından sorgulanma durumları soruldu. Veriler tanımlayıcı istatistik ve ki-kare testiyle değerlendirildi. BULGULAR: Katılımcıların yaş ortancası 40 (25.p; 32-75.p;52) idi ve 76,4%‟ü kadın iken, 50,4%‟ü kilolu, 20,8%‟i obezdi. Katılımcıların 36,2%‟si sigara kullanıyordu, 22,0%‟si hipertansifti ve 10,4%‟ü hiperglisemikti. Kaçırılmış fırsatlar obezite ve kan kolesterol düzeylerinin sorgulanmasıyla ilgili yaklaşık 90,0%, hipertansiyonla ilgili 70,0% ve diyabetle ilgili 85,0% idi. SONUÇ: Sağlık ocağında kronik hastalıklar ve risk faktörleriyle ilgili fırsatlar kaçırılmakta ve risk faktörlerinin sorgulanması ihmal edilmektedir.

AIM: The aim of the study was to investigate missed opportunities about chronic diseases and related risk factors in a primary health care center in Istanbul. METHOD: This descriptive study was held in a Primary Health Care Center in Istanbul with the study population consisted of 500 people which were applicated in one month period. Participants were asked; if they were questioned by their physician about major risk factors (smoking, obesity, diabetes mellitus, hypertension, coroner heart disease in family, glysemic level, cholesterol level) and regular exercise practice according to Primary Care 2006 Guidelines. The data was evaluated by descriptive statatistics, chi square test. RESULTS: The median age of the participants were 40 (25.p; 32-75.p;52) and 76.4% of them were female. 50.4% of participants were overweight, 20.8% of them were obese. 36.2% of them were smoking, 22.0% were hypertensive, 10.4% were hiperglysemic. There were around 90.0% missing opportunities screening and management of obesity and blood cholesterol level, 70.0% about hypertension and 85.0% about diabetes. CONCLUSION: Opportunities about chronic diseases and their risk factors are being missed and asking about risk factors are neglected in primary health care center.
[Missed opportunities for chronic diseases prevention in a primary health care center in Istanbul]
Keywords: Sağlık Bilimleri ve Hizmetleri; Genel ve Dahili Tıp; Temel Sağlık Hizmetleri